Populizm na łamach „Faktu” - Czajka-Bubniak, Anna (Słowo. Studia językoznawcze, 2015)
Tabloid “Fact” is concerned on fulfilling simple readers expectations. According to research, simple reader is characterized as a middle-aged inhabitant of town or village, rather working in services and sector trade. Then, tabloid is seen as a newspaper defending an average citizen and accusing authorities (called elites). Our society is functioning around two opposites: good – bad, rich – poor. An average citizen is created as a persecuted by a richer part of society. Tabloid expresses voice of the people by the popular slogans. The main aim of the article is researching what popular slogans are most characteristic for the tabloid. A reader is the centre of tabloid attention.